Diversity and distribution of ectoparasite taxa associated with Micaelamys namaquensis (Rodentia: Muridae), an opportunistic commensal rodent species in South Africa. Issue 9 (1st August 2022) - Stevens, L.; Stekolnikov, A. A.; Ueckermann, E. A.; Horak, I. G.; Matthee, S.
Abstract: Abstract: South Africa boasts a rich diversity of small mammals of which several are commensal and harbour parasites of zoonotic importance. However, limited information is available on the parasite diversity and distribution associated with rodents in South Africa. This is particularly relevant for Micaelamys namaquensis (Namaqua rock mouse), a regionally widespread and locally abundant species that is often commensal. To address the paucity of data, the aims of the study were to record the ectoparasite diversity associated with M. namaquensis and develop distribution maps of lice and mites associated with M. namaquensis and other rodents in South Africa. Micaelamys namaquensis individuals ( n = 216) were obtained from 12 localities representing multiple biomes during 2017–2018. A total of 5591 ectoparasites representing 5 taxonomic groups – fleas, lice, mesostigmatid mites, chiggers and ticks was recorded. These consisted of at least 57 taxa of which ticks were the most speciose (20 taxa). Novel contributions include new host and locality data for several ectoparasite taxa and undescribed chigger species. Known vector species were recorded which included fleas ( Ctenocephalides felis, Dinopsyllus ellobius and Xenopsylla brasiliensis ) and ticks ( Haemaphysalis elliptica, Rhipicephalus appendiculatus and Rhipicephalus simus ). Locality records indicate within-taxon geographic differences between the 2 louse species and the 2 most abundant mite species. It is clear that M. namaquensis hosts a rich diversity of ectoparasite taxa and, as such, is an important rodent species to monitor in habitats where it occurs in close proximity to humans and domestic animals.